AFFECTIVE MEANS OF REPRESENTATION OF THE CONCEPT “FELICIDAD” IN THE MODERN SPANISH LINGUISTIC WORLD VIEW - Misiurak, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article studies the affective means of expressing the concept of “felicidad” in the modern Spanish-speaking worldview on the basis of Spanish corpora. This article examines the linguistic means that convey the emotional content of the concept of “happiness” through various means of linguistic expression. Examples emphasizing the cultural peculiarity of the perception of happiness in Spanish-speaking society are analyzed, and the relationship between language and emotional experience is revealed. The study's results contribute to a deeper understanding of the linguistic and cultural specificity of the concept of “felicidad” and its reflection in the modern Spanish language._____________ Література:• Вільчинська Т. П. Основні підходи до визначення концепту в лінгвістичній парадигмі. Наукові записки Тернопільського національного педагогічного університету. 2009. № 2. С. 26–33. URL: http://dspace.tnpu.edu.ua/bitstream/123456789/19733/1/vilchynska_ 26-33.pdf• Загнітко А. П. Сучасний лінгвістичний словник. Вінниця : Твори, 2020. 920 с. URL: https://r.donnu.edu.ua/xmlui/bitstream/handle/123456789/469/Словник_RD-Суч_лінгв_ словник%20(1).pdf?sequence=1&isAllowed=y• Загнітко А. Сучасні типології концептів : когнітивний, лінгвокультурологічний, прагматичний аспекти. Науковий вісник Херсонського державного університету. Серія: Лінгвістика. 2010. Вип. ХІ. С. 33–46. URL: http://www.irbis-nbuv.gov.ua/cgi-bin/irbis_nbuv/cgiirbis_ 64.exe?I21DBN=LINK&P21DBN=UJRN&Z21ID=&S21REF=10&S21CNR=20&S21STN=1&S21FMT=ASP_meta&C21COM=S&2_S21P03=FILA=&2_S21STR=lingst_2010_21_4• Заньковська Г. Д. Методи дослідження концептів. Науковий вісник Міжнародного гуманітарного університету. 2015. Т. 2, № 19. С. 102–104. URL: http://www.vestnik-philology.mgu.od.ua/archive/v19/part_2/29.pdf• Полюжин М. М. Поняття, концепт та його структура. Науковий вісник Східноєвропейського національного університету імені Лесі Українки. 2015. № 4. С. 212–222. URL: http://nbuv.gov.ua/UJRN/Nvvnuflm_2015_4_43• Полюжин М. М. Типологія й аналіз концептів. Іноземна філологія. 2009. Вип. 121. С. 80–89.• Приходько А. Т. Концепти і концептосистеми в когнітивно-дискурсивній парадигмі лінгвістики. Запоріжжя: Прем'єр, 2008. 332 с.• Семененко Л. Л. Від концепту до значення слова. Наукові записки Національного університету "Острозька академія". 2015. № 58. С. 18–20. URL: http://nbuv.gov.ua/UJRN/Nznuoaf_2015_58_9• Слободян М. В. Концепт як одиниця когнітивних досліджень. Наукові записки Національного університету «Острозька академія». 2010. № 16. С. 276–284. URL: http://nbuv.gov.ua/ UJRN/Nznuoaf_2010_16_46• Corpus del Español (CEsp) – Mark Davies. URL: https://www.corpusdelespanol.org/now/• Corpus de Referencia del Español Actual (CREA) – Real Academia Española. URL: http://corpus.rae.es/creanet.html• Diccionario de la lengua española. RAE. Edición del Tricentenario. Madrid, 2022. URL: https://www.rae.es/
Keywords: affective language means, the concept of “felicidad”, the Spanish linguistic worldview, emotional expressions, metaphor, epithets, cultural peculiarity, language corpora